THE EFFICACY OF NURSE-LED HEALTH PROMOTION INTERVENTIONS IN SCHOOLS - Amal Jupran Sofy, Abdulrhman Saleem Aldafeiri, Fatimah Ahmad Sadly, Kamlah Mohammed Shajri, Faisal Hassan Mawkili, Maram Jaber Alrowaily, Hassan Saeed Aldawsari, Amnah Aziz Alsubaie, Radhyah Hassan Alfaifi, ,; Saeed Abdullah Aldawsari, Emtiaz Mohammad Mobaraky, Owaidh Mathkar Owaidh Almutairi, Obaid Saad Aldossari, Abdulrahman Mohammed Homadi, Reem Masad Matar Almoteri, (Chelonian Research Foundation, 2022)
School nurses engage in proactive measures to enhance the physical and intellectual well-being of pupils by interacting with students, parents, and school personnel. We performed an integrated literature analysis of existing research to outline the various kinds of interventions carried out by school nurses, as well as the educational and health outcome measures. Additionally, we investigated the correlation between school nurse interventions and student outcomes. A total of sixty-five studies satisfied the inclusion criteria. We used the National Association of School Nurses' Framework for the Twenty-First Century School Nursing Practice to classify school nurse interventions and assess health and education outcome metrics. Most of the treatments were classified under the idea of care coordination, with motivating interviews and counseling being the most frequently used approaches. Seventeen research have shown a correlation between school nurse interventions and enhanced student outcomes. The majority of studies (80%) were of a descriptive nature. In order to further develop the field of school nursing science, scholars may enhance the existing knowledge by using more rigorous research methodologies to assess the effects of school nurse activities and interventions on the health and educational outcomes of students.